Together We Can Face On: Co-parenting and Parental Stress on Mothers During the Covid 19 Pandemic - Nida Muthi Annisa; Cahyaning Widhyastuti; Putri Yohannida Aulia Fadhilla (Research Collaboration Community (RCC), 2023)
A mother becomes a figure who has a central role in the family, one of which is in terms of parenting. However, when carrying out the role of parenting, it is not always easy. Difficult conditions and situations will be encountered and allow stress to arise. The situation difficulty coupled with the occurrence of the covid-19 pandemic causes all activities to be carried out at home and adds to the work to become children's learning companions and to take care of family needs. The condition can make the mother feel pressure for the demands faced, causing stress. Looking at this, the researchers assessed a thing that can affect the stress of mothers when raising children (parental stress) is the involvement of partners in parenting (co-parenting). This study aims to prove, namely how the effect of co-parenting on parental stress in mothers, especially during the covid-19 pandemic. In the process, this study involved 62 mothers as research respondents by providing research questionnaires. The research questionnaire consisted of a co-parenting scale and a parental stress scale. The results of data analysis obtained by simple regression analysis showed that there was an effect of co-parenting on parental stress in mothers during the covid-19 pandemic (p < 0.05). The output are that the role of partners in working together to care for and care for children can reduce the stress felt by mothers.